(untitled) (Brazilian Journal of Radiation Sciences, 2019)
The aim of this work is study on the recycling process of zirconium alloy chips and the results aiming the efficiency in the cleaning process; the quality control; the obtaining of the pressed electrodes and finally the melting in a Vac-uum Arc Remelting furnace (VAR). The recycling process begins with magnetic separation of possible ferrous al-loys chips contaminant, the washing of the cutting fluid that is soluble in water, washing with an industrial degreas-er, followed by a rinse with continuous flow of water under high pressure and drying with hot air. The first evalua-tion of the process was done by an Energy Dispersive X-rays Fluorescence Spectrometry (EDXRFS) showed the presence of 10 wt. % to 17 wt. % of impurities due the mixing with stainless steel machining chips. The chips were then pressed in a custom-made matrix of square section (40 x 40 mm - 500 mm in length), resulting in electrodes with 20% of apparent density of the original alloy. The electrode was then melted in a laboratory scale VAR furnace at the CCTM-IPEN, producing a massive ingot with 0.8 kg. It was observed that the samples obtained from In-dústrias Nucleares do Brasil (INB) are supposed to be secondary scrap and it is suggested careful separation in the generation of this material. The melting of the chips is possible and feasible in a VAR furnace which reduces the storage volume by up to 40 times of this material, however, it is necessary to correct the composition of the alloy for the melting of these ingots.